Two new species and new records in the alpheid shrimp genera Salmoneus Holthuis, 1955 and Deioneus Dworschak, Anker & Abed-Navandi, 2000 in the Atlantic Ocean (Malacostraca: Decapoda) - Anker, Arthur (Zootaxa, 2020)
The present study deals with two species new to science, as well as several new records in the closely related alpheid shrimp genera Salmoneus Holthuis, 1955 and Deioneus Dworschak, Anker & Abed-Navandi, 2000, based on material collected at various localities in the tropical western and eastern Atlantic Ocean. In the western Atlantic, Salmoneus inconspicuus sp. nov. is described based on material from the Caribbean coast of Panama, Cuba, French Antilles and (with some doubts) Bermuda. The new species has been previously reported from the eastern Caribbean Sea as S. teres Manning & Chace, 1990, a closely related species so far known only from Ascension Island in the central Atlantic. Salmoneus camaroncito Anker, 2010 is reported from the Caribbean coast of Mexico, for the first time since its original description. Salmoneus carvachoi Anker, 2007 is reported from Colombia and southeastern USA, representing a new record of the species for each of these countries. Salmoneus depressus Anker, 2011 and Salmoneus setosus Manning & Chace, 1990 are reported for the first time from Cuba and Panama, respectively. In addition, these two species, as well as Salmoneus wehrtmanni Anker, 2010, are reported from new localities in Mexico. In the eastern Atlantic, Salmoneus saotomensis sp. nov. is described based on a single specimen from São Tomé Island in the Gulf of Guinea. The new species is characterised by the somewhat enlarged minor cheliped and is compared to all other Atlantic species presenting this feature. Deioneus sandizelli Dworschak, Anker & Abed-Navandi, 2000 is reported from São Tomé Island, for the first second time since its original description based on the Cape Verde type material. The characters separating Deioneus and Salmoneus are reassessed. The new evidence shows that these two genera are distinguished by only one morphological feature known to be variable in at least one non-related alpheid genus. However, in view of the increasing morphological heterogeneity in Salmoneus, it seems more appropriate to retain Deioneus as a valid genus for it may represent a distinct clade that also includes several other species currently placed in Salmoneus.